2022
DOI: 10.1111/pbr.13068
|View full text |Cite
|
Sign up to set email alerts
|

Induction of polyploids in acid lime (Citrus aurantifolia) through colchicine treatment of in vitro derived shoot tip explants

Abstract: Polyploid breeding is an effective tool to induce variability in the existing population, specifically in the crops having very narrow genetic base such as acid lime. Hence, an experiment was conducted to induce polyploidy in acid lime through colchicine treatment. Higher frequency of triploids were obtained in 250 μM colchicine treatment (27.27%), whereas combination of 3× (21.42%), 4× (13.33%) and aneuploid (6.67%) were induced at 500 μM colchicine treatment. Measurement of stomatal density and guard cell si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…The decreased stomatal density and increased dimensions might be due to induced mutation occurrences or ploidy level changes. These findings align with earlier studies (Blasco et al, 2015;Bhuvaneswari et al, 2020;Suliman et al, 2020;Usman et al, 2021;Kashtwari et al 2022;Bora et al, 2023) conducted on loquat, lemon, citrange, black locust, grapefruit, saffron and acid lime. The data presented in Fig.…”
Section: Resultssupporting
confidence: 92%
“…The decreased stomatal density and increased dimensions might be due to induced mutation occurrences or ploidy level changes. These findings align with earlier studies (Blasco et al, 2015;Bhuvaneswari et al, 2020;Suliman et al, 2020;Usman et al, 2021;Kashtwari et al 2022;Bora et al, 2023) conducted on loquat, lemon, citrange, black locust, grapefruit, saffron and acid lime. The data presented in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Due to the randomness of mutations caused by asexual polyploidy, plant tissues may contain hybrids or chimeras. In this study, we also found chimeras as reported in other different crops [ 22 ]. Generally, colchicine disrupts mitosis by preventing microtubule polymerization, resulting in inhibition in polar migration of chromosomes at anaphase.…”
Section: Discussionsupporting
confidence: 89%
“…More importantly, it is possible to improve mutagenesis efficiency and reduce chimerism [ 20 ]. Therefore, polyploidization can drive plant evolution and domestication through chromosome doubling [ 21 ] and it is an effective tool to induce variability in the existing population [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation